The American Academy of Health Behavior 2017 Annual Scientific Meeting: "Health Behavior Research in the Age of Personalized Medicine" - AAHB Board and 2017 Conference Committee (New Prairie Press, 2017)
The American Academy of Health Behavior (AAHB) hosted its Annual Scientific Meeting at Loews Ventana Canyon in Tucson, AZ March 19-22, 2017. The theme of the meeting was "Health Behavior Research in the Age of Personalized Medicine." This publication describes the meeting theme, podium presentations and workshop, and includes the refereed abstracts presented at the 2017 Annual Scientific Meeting.